Relating academic performance to L1 and L2 learners' scores on the SDRT and Raven's SPM - Gangat, Nabeela (My University, 2017)
This research study investigated the relationship between first (L1) and second language (L2) learners’ academic performance and their scores on the Stanford Diagnostic Reading Test (SDRT) and the Raven’s Standard Progressive Matrices (RSPM). The inherently different nature of using a verbal assessment and a non-verbal assessment are important to consider in relation to overall academic performance, especially in light of the different language demands of a verbal versus a non-verbal assessment. South Africa has a diverse language landscape, which does pose practical problems for choosing a standard language of learning and teaching, which could create some language issues. The concept of intelligence is unpacked and discussed in relation to both academic performance and reading, which requires careful navigation due to its links to both these concepts. Psychological testing and assessment in South Africa has an encumbered history, which makes research in this area valuable, especially in relation to the unique language diversity in South Africa combined with the lack of South African assessments . Language, reading and intelligence are important to consider in light of the role they to play in relation to overall academic achievement. The results revealed that L1 learners performed better compared to L2 learners on both the SDRT and the RSPM. L1 learners also performed better academically compared to their peers. These results indicated some serious implications showing that L2 learners have not been able to bridge language and learning gaps, after at least five years of being taught in English. The results also revealed that the SDRT was a better predictor of academic performance for both L1 and L2 learners. This highlighted the importance of reading within the South African school system. The under researched area of the exact impact that reading has on overall academic performance showed that South Africa’s curriculum is reading heavy, which does emphasise the importance of reading to achieve academic success.
A Research Report submitted to the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Education in Educational Psychology by Coursework and Research Report. Johannesburg, March 2017
Keywords: Reading--Ability testing--South Africa; Academic achievement--South Africa; English language--Study and teaching--South Africa; Educational psychology--South Africa